The history of concepts of Reinhart Koselleck: Fundamental concepts, sattelzeit and historik - Blanco Rivero, José Javier (2018)
In this article, I will primarily assess the foundations of Reinhart Koselleck’s historiography. First, I will discuss the foundations of conceptual history and its relevance to social history, as well as his time strata theory, his most transcendental work. Second, I will appraise Koselleck’s thesis of a saddle period (Sattlelzeit) accounting for the acceleration of his- tory, and having political and social consequences in Europe. Then, I will explain his theory of conditions of possible histories (Historik), which he draws on philosophical anthropology and Martin Heidegger’s existentialism. Finally, I will provide a critical balance of the analytical advantages and issues of his work, and conclude that Koselleck’s theory of time strata is his most important contribution to historiography. This paper is conceived of as a contribution to the dissemination in Venezuela of the work of this German thinker.